Discovery of Guanfacine as a Novel TAAR1 Agonist: A Combination Strategy through Molecular Modeling Studies and Biological Assays - Elena Cichero; Valeria Francesconi; Beatrice Casini; Monica Casale; Evgeny Kanov; Andrey S. Gerasimov; Ilya Sukhanov; Artem Savchenko; Stefano Espinoza; Raul R. Gainetdinov; Michele Tonelli (MDPI AG, 2023)
Trace amine-associated receptor 1 (TAAR1) is an attractive target for the design of innovative drugs to be applied in diverse pharmacological settings. Due to a non-negligible structural similarity with endogenous ligands, most of the agonists developed so far resulted in being affected by a low selectivity for TAAR1 with respect to other monoaminergic G protein-coupled receptors, like the adrenoreceptors. This study utilized comparative molecular docking studies and quantitative-structure activity relationship (QSAR) analyses to unveil key structural differences between TAAR1 and alpha2-adrenoreceptor (α2-ADR), with the aim to design novel TAAR1 agonists characterized by a higher selectivity profile and reduced off-target effects. While the presence of hydrophobic motives is encouraged towards both the two receptors, the introduction of polar/positively charged groups and the ligand conformation deeply affect the TAAR1 or α2-ADR putative selectivity. These computational methods allowed the identification of the α2A-ADR agonist guanfacine as an attractive TAAR1-targeting lead compound, demonstrating nanomolar activity in vitro. In vivo exploration of the efficacy of guanfacine showed that it is able to decrease the locomotor activity of dopamine transporter knockout (DAT-KO) rats. Therefore, guanfacine can be considered as an interesting template molecule worthy of structural optimization. The dual activity of guanfacine on both α2-ADR and TAAR1 signaling and the related crosstalk between the two pathways will deserve more in-depth investigation.